Neuroprotection by cannabidiol and hypothermia in a piglet model of newborn hypoxic-ischemic brain damage. (1st March 2019) - Barata, Lorena; Arruza, Luis; Rodríguez, Maria-José; Aleo, Esther; Vierge, Eva; Criado, Enrique; Sobrino, Elena; Vargas, Carlos; Ceprián, María; Gutiérrez-Rodríguez, Ana; Hind, William; Martínez-Orgado, José
Abstract: Objective: Hypothermia, the gold standard after a hypoxic-ischemic insult, is not beneficial in all treated newborns. Cannabidiol is neuroprotective in animal models of newborn hypoxic-ischemic encephalopathy. This study compared the relative efficacies of cannabidiol and hypothermia in newborn hypoxic-ischemic piglets and assessed whether addition of cannabidiol augments hypothermic neuroprotection. Methods: One day-old HI (carotid clamp and FiO2 10% for 20 min) piglets were randomized to vehicle or cannabidiol 1 mg/kg i.v. u.i.d. for three doses after being submitted to normothermia or 48 h-long hypothermia with a subsequent rewarming period of 6 h. Non-manipulated piglets (naïve) served as controls. Hemodynamic or respiratory parameters as well as brain activity (aEEG amplitude) were monitored throughout the experiment. Following termination, brains were obtained for histological (TUNEL staining, apoptosis; immunohistochemistry for Iba-1, microglia), biochemical (protein carbonylation, oxidative stress; and TNFα concentration, neuroinflammation) or proton magnetic resonance spectroscopy (Lac/NAA: metabolic derangement; Glu/NAA: excitotoxicity). Results: HI led to sustained depressed brain activity and increased microglial activation, which was significantly improved by cannabidiol alone or with hypothermia but not by hypothermia alone. Hypoxic-ischemic-induced increases in Lac/NAA, Glu/NAA, TNFα or apoptosis were not reversed by either hypothermia or cannabidiol alone, but combination of the therapies did. No treatment modified the effects of HI on oxidative stress or astroglial activation. Cannabidiol treatment was well tolerated. Conclusions: cannabidiol administration after hypoxia-ischemia in piglets offers some neuroprotective effects but the combination of cannabidiol and hypothermia shows some additive effect leading to more complete neuroprotection than cannabidiol or hypothermia alone. Highlights: Neither hypothermia nor CBD alone reduced brain damage in asphyxiated piglets. Administration of CDB alone led to some functional beneficial effects. Combining hypothermia and CBD led to robust neuroprotective effects. Combining hypothermia and CBD modulated excitotoxicity and inflammation.